A study on practices and awareness of safety and health aspect in Giat Mara Centre / Wan Mohammad Ariff Wan Kamaruddin - Wan Kamaruddin, Wan Mohammad Ariff (Faculty of Architecture, Planning and Surveying, 2013)
Giat Mara is one of the skilled institutions under the Majlis Amanah Rakyat (MARA). The Giat Mara Center provides an alternative route for the Malaysian community to gain their skill and knowledge. This descriptive study aims to look at comprehensive and workshop safety and health practice among Giat Mara students covering regulation, environments, responsibility, and use of hand tools, machinery aspects and health. Technical workshops are typically considered are highly hazardous places in the giat mara centre when addressing the problem of high incidence and fatality rates. In conjunction with several topics covered in the technical curricular, safety and health precaution should be highlighted in order to connect too few key ideas of being safe. Therefore the assessment of safety awareness in term of safety and health about hazardous and risks at workshop is needed and has to be incorporated with technical education and other training programmers. The result of the study has found that there was a significant correlation between safety and health practices and students awareness on safety and health. Sample of 60 respondents were taken for the purpose of this study from Giat Mara Centre, Technology of Automotive Certificate in Malaysia. The methodology used in this study are based on panels and questionnaire survey. The study showed panels and students awareness about safety are at high level. Even so, the health aspects are less practiced by students. Thus, several proposed have been identified to the Giat Mara Centre can be exposed to increased awareness and practice safety workshop environment among students